Transmissible Mink Encephalopathy: Studies on the Peripheral Lymphocyte - Marsh, R. F. (1973)
Circulating lymphocytes from mink with transmissible mink encephalopathy were studied for the presence of virus particles and for infectivity. Electron microscope examination of phytohemagglutinin-stimulated lymphocyte cultures revealed no evidence of virus-like particles. Circulating lymphocytes were also found to be noninfectious when the transmissible agent could be demonstrated in intact lymphoid organs in infected mink. A lymphopenia was detected in affected mink during the late clinical stage of disease, but this was most likely a secondary effect due to a terminal stress factor.